Exploring the Impact of English Movies to Improve the Students’ Listening Comprehension - Hermansyah, Sam; Hasan, Hasan (Majesty Journal, 2020)
The objective of this research was to improve the listening comprehension of the students of SMPN 1 Maiwa by using English Movies. The research aimed to see if English movies can improve the listening skills of students and to find out how students are using English Movies to increase their listening skills. The pre-experimental method was used. Students from SMPN 1 Maiwa in 2018/2019, which comprises 20 students, were part of the research. Ten first-class students and 10 second-class students. In taking the sample, the author used a random sample. The researcher used data collection methods and questionnaires. The researcher has distributed listening tests by pre-testing and post-testing and sent questionnaires to gather information on their attitudes towards using English movies. Work suggests that the listening abilities of the students were poor in the preliminary examination. Their ability to listen is considerably increased after therapy. From their score, it can be seen that changed well. The findings evaluated with the t-test suggest that the t-test value is higher than the t-table (7.98>2.093). English Movies can be concluded to develop the listening skills of students.